Impact of bio-based binders on rheological properties of aqueous alumina slurries for tape casting. Issue 11 (September 2021) - Marie, Jérémy; Bourret, Julie; Geffroy, Pierre-Marie; Chartier, Thierry; Bienia, Marguerite; Chaleix, Vincent; Picton, Luc; Smith, Agnès
Abstract: This work describes the preparation of concentrated alumina suspensions based on bio-sourced additives with a low environmental impact and with the rheological properties adapted to the tape casting process. Natural polysaccharides extracted from plants and fruits (pectin, psyllium…) were characterized (molar weight) and identified as promising binders for substituting the classical organic binders from petrochemical industry. The rheological behavior of the additives and of the suspensions containing these bio-sourced additives was studied in flow and in oscillations. The mechanical properties of the green tapes obtained with the different bio-sourced binders were determined from tensile experiment. This paper studies the relations between the nature of the binder, the rheological behavior of the suspension, the ability to tape cast the suspensions and the final properties of the green and sintered tapes.